Seminal characteristics of Curraleiro and Holstein bulls submitted to scrotal insulation - Pezzini, Tomaz Gelson; Sartori, Roberto; Silva, Thiago Antônio de Souza Nascimento; McManus, Concepta; Mariante, Arthur da Silva (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to compare the adaptation to high temperatures of a Brazilian local breed with an European one. The effects of scrotal insulation for 48 hours on seminal characteristics of Curraleiro (n = 5) versus Holstein (n = 6) bulls were evaluated. A sequence of semen collection and andrologic evaluation was performed before (two collections) and after (nine weekly collections) scrotal insulation. Among the seminal parameters evaluated, the progressive sperm motility had a significantly lower decrease in Curraleiro (25%) than in Holstein bulls (50%), during the postinsulation period. Sperm motility of Curraleiro bulls, 37 days after insulation, returned to pre-insulation values sooner than that of Holstein bulls (51 days). Sperm vigor had a lower decrease after insulation in Curraleiro (15.2%) than in Holstein bulls (47.8%). The total number of spermatozoa per ejaculate has dropped similarly in both groups after scrotal insulation (67.9 and 79.4% of drop for Curraleiro and Holstein bulls, respectively, between 16 and 23 days). The percentage of abnormal spermatozoa reached maximum values between 16 and 30 days after insulation and was greater in Holstein bulls (41.3±5.9%) 30 days after the insult. Curraleiro are more tolerant to the effects of scrotal insulation on seminal characteristics than Holstein bulls.